How to find gold - Schwarz, Viviane (Somerville, Massachusetts : Candlewick Press, 2016)
Anna and her friend Crocodile set off on an adventure to find sunken gold, even though it is a dangerous and difficult quest.
Keywords: Treasure troves -- Juvenile fiction; Imagination -- Juvenile fiction; Friendship -- Juvenile fiction; Adventure stories; Picture books